2004
DOI: 10.1111/j.0906-7590.2005.03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil phytoliths as evidence for species replacement in grazed rangelands of central Argentina

Abstract: Iglesias, R. M. 2004. Soil phytoliths as evidence for species replacement in grazed rangelands of central Argentina. Á/ Ecography 27: 725 Á/732.Rangeland utilization for livestock production in central Argentina has apparently resulted in the replacement of preferred mid-grasses (Poa ligularis and Stipa clarazii ) by preferred short-grasses (Piptochaetium napostaense and Stipa tenuis ) and avoided grasses (Stipa tenuissima and Stipa eriostachya ). However, the botanical composition in the pristine condition is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 34 publications
1
22
0
2
Order By: Relevance
“…Functional groups were the same with Fig. 2 are excluded for ten or more years (Distel and Boo 1996;Moretto and Distel 1997;Gallego et al 2004). In concordance, graminoids and sedge species, which dominate in alpine community and are palatable for herbivores, showed significant improvement in fenced meadows.…”
Section: Discussionmentioning
confidence: 99%
“…Functional groups were the same with Fig. 2 are excluded for ten or more years (Distel and Boo 1996;Moretto and Distel 1997;Gallego et al 2004). In concordance, graminoids and sedge species, which dominate in alpine community and are palatable for herbivores, showed significant improvement in fenced meadows.…”
Section: Discussionmentioning
confidence: 99%
“…This is also related to a stronger growth and competitive advantage shown by Elymus nutans. Previous research has reported that palatable grasses have greater competitive ability and show a greater increase in abundance in grasslands than unpalatable grasses where livestock are excluded (Distel and Boo 1996;Moretto and Distel 1997;Gallego et al 2004). Furthermore, palatable grasses which had higher productivity and quality can lock abundant nutrients within their tissues from the soil (Moretto and Distel 1997;Harris et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2008) found that long-term exclusion of livestock grazing can significantly improve soil nutrient properties and soil organic carbon in grassland community of the Loess Plateau. Conversely, improvement of soil nutrient conditions in grassland can promote the growth of plant species and biomass accumulation, especially for palatable grasses which have greater competitive ability than unpalatable grasses (Gallego et al 2004). Wu et al (2009) found that nine-year exclusion of livestock grazing had negative consequences for biodiversity because it led to a reduction of plant density and species diversity in an alpine grassland community.…”
Section: Grassland Types Grassland Typesmentioning
confidence: 99%